ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN PELABUHAN MUARA ANGKE - Fadliyah Nurbaya; Winoto Hadi (Universitas Negeri Jakarta, 2020)
The port has an important role in serving activities in one of the archipelago countries, Indonesia. The availability of services contained in ports for users of port services must be considered by the government which is excepted to be able to try to meet the level of port service performance expected of the high level of satisfaction of users of port service in DKI Jakarta. The policy of the DKI Jakarta Provincial Government in the field of transportation, especially in the department of transportation, the Unit for Management of water and Port Transportation. The services contained in the port that can be directly felt by users of port services are those that are available at the passenger port. One of the passanger ports in DKI Jakarta that is expected to provide a high level of satisfaction is Muara Angke Passanger Port. This research technique uses survey methods for sampling data, analysis of the discussion using descriptive analysis, gap method by calculating the level of suitability and cartesius diagram. As a result, users of port services are still not maximal in providing services in ports such as there is no service to provide information on emergency health care facilities and there is no convenience service for health services aimed at anticipating healt emergencies, so that users of port service immediateky receive help first.